2022
DOI: 10.3390/biology11101500
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-Level Assembly of Male Opsariichthys bidens Genome Provides Insights into the Regulation of the GnRH Signaling Pathway and Genome Evolution

Abstract: The hook snout carp Opsariichthys bidens is an important farmed fish in East Asia that shows sexual dimorphism in growth, with males growing faster and larger than females. To understand these complex traits and improve molecular breeding, chromosome-level genome assembly of male O. bidens was performed using Illumina, Nanopore, and Hi-C sequencing. The 992.9 Mb genome sequences with a contig N50 of 5.2 Mb were anchored to 38 chromosomes corresponding to male karyotypes. Of 30,922 functionally annotated genes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Previous genomic studies showed that the haploid chromosome number of this species varied between sexes, e.g. females had 39 chromosomes while males 38 chromosomes [43] , [95] . However, in our study, the female O. bidens also carried 38 chromosomes, suggesting sex may be not the major determinant of chromosome number variation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous genomic studies showed that the haploid chromosome number of this species varied between sexes, e.g. females had 39 chromosomes while males 38 chromosomes [43] , [95] . However, in our study, the female O. bidens also carried 38 chromosomes, suggesting sex may be not the major determinant of chromosome number variation.…”
Section: Discussionmentioning
confidence: 90%
“…Carp O. bidens is known for its ability to grow fast and adapt well to both the field and farming environment, making it an ideal species to investigate adaptation and fast evolution [101] , [106] , [14] , [46] . Currently, genomic studies on O. bidens have largely focused on chromosome evolution and adaptive radiation [22] , [43] , [95] . However, little is known about the molecular evolutionary rate of O. bidens and the underlying determinants.…”
Section: Introductionmentioning
confidence: 99%
“…7 B), as this signaling pathway can take a vital role in the control of reproductive function, growth and development of fishes (Okubo and Nagahama 2008 ). Also, Liu et al ( 2022a , b ) have found that this signaling pathway in male Opsariichthys bidens was able to induce the action of growth hormone in males by regulating the secretion of luteinizing hormone and glycoprotein hormone, making males grow faster than females (Liu et al 2022b ). In addition, we identified the Notch signaling pathway that may be directly related to the adaptive evolution of K. punctatus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Boars require castration during the pig breeding process, as male hormones will accumulate in their bodies after growing to a certain age, causing odor and negatively affecting the flavor and taste of pork. The gonadotropin-releasing hormone GnRH plays a crucial role in animal growth and reproduction by stimulating the pituitary synthesis and secretion of gonadotrophic hormone in the head ( 3 ). Multiple factors influence animal reproduction both in vivo and in vitro , including positive and negative feedback, where the hypothalamic–pituitary-gonadal axis plays an important role, while GnRH is the most critical ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%